2010
DOI: 10.1007/s00266-010-9615-6
|View full text |Cite
|
Sign up to set email alerts
|

Defining Pseudoptosis (Bottoming Out) 3 Years After Short-Scar Medial Pedicle Breast Reduction

Abstract: Three-dimensional photography is a useful tool enabling the plastic surgeon to monitor the postoperative changes in breast morphology objectively. This study provides quantifiable data demonstrating that pseudoptosis and tissue redistribution are limited to the initial postoperative year for patients undergoing short-scar medial pedicle breast reduction. The kinetic change in the breasts during postoperative years 2 and 3 appears to be minimal. Studies comparing the changes in morphology over time with differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…Volume loss occurred during the first year and, again, they demonstrated that the percent of tissue in the upper pole decreased from 76% to 69%, illustrating the 'bottoming out' phenomenon which was described in another of their publications [95]. A subsequent study by the group demonstrated that between post-operative years one and three there was no further significant volume loss or further redistribution of the breast tissue [96]. The authors concluded that by compiling a series of actual changes post-operatively using 3D-SI it may be possible to provide guidelines for pre-operative planning.…”
Section: Quantifying Post-operative Changes Over Timementioning
confidence: 85%
“…Volume loss occurred during the first year and, again, they demonstrated that the percent of tissue in the upper pole decreased from 76% to 69%, illustrating the 'bottoming out' phenomenon which was described in another of their publications [95]. A subsequent study by the group demonstrated that between post-operative years one and three there was no further significant volume loss or further redistribution of the breast tissue [96]. The authors concluded that by compiling a series of actual changes post-operatively using 3D-SI it may be possible to provide guidelines for pre-operative planning.…”
Section: Quantifying Post-operative Changes Over Timementioning
confidence: 85%
“…Quan et al [ 16 ], while studying the changes in breast morphology 3 years after cosmetic breast surgery, noticed that during the early to 1-year postoperative period, the tissue is redistributed from the superior pole to the inferior pole of the breast leading to bottoming out. This observation concurs with Flowers' [ 17 ] suggestion.…”
Section: Discussionmentioning
confidence: 98%
“…Breast reduction is a very common procedure done to relief both physical and emotional problems in women with large breasts [5]. Apart from improving symptoms, the goal of surgery should attain aesthetically pleasing breasts with minimal scarring and preservation of NAC sensation [6].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors used measurements such as SN-N distance to judge the changes that occur in NAC position and the N-IMF distance for bottoming out evaluation [11][12][13]. Others used 3D imaging and computer software for evaluation of breast volume changes, redistribution of breast tissue from upper to lower pole and breast projection [6,14].…”
Section: Discussionmentioning
confidence: 99%